Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) of Wood polymer nanocomposites - Md. Rezaur, Rahman; Sinin, Hamdan; Lai, Josephine Chang Hui (EDP Sciences, 2017)
This study evaluates the thermal property of clay dispersed Styrene-co-Glycidal Methacrylate impregnated wood polymer nanocomposite (WPNC). The WPNC was characterized by FTIR, TGA and DSC methods. FT-IR result showed that the absorbance of wave number at 1730 cm−1, increased for clay dispersed Styrene-co-Glycidyl Methacrylate wood polymer nanocomposite (ST-co-GMA-clay-WPNC). From TGA, ST-co-GMA-clay-WPNC showed better thermal stability at the temperature below 450oC. The final weights of ST-co-GMA-clay-WPNC and ST-Clay-WPNC, between 420 and 700oC, were significantly less than the raw wood. When the temperature was below 450oC, nanoclay-incorporated surface modified wood composites showed enhanced higher thermal properties compared with those without nanoclay. From DSC, the degradation enthalpy at around 360oC of ST-co-GMA-Clay- WPNC was the highest.